Collaborating With Parents to Increase Proactive Bystander Messages. Issue 1 (January 2020) - Banks, Courtney S.; Blake, Jamilia J.; Lewis, Katherine
School antibullying initiatives are increasingly focused on educating students about the impact of proactive bystanders to reduce victimization. However, according to the social-ecological perspective, children can also choose to adopt bystander responses based on what their parents teach them at home. School counselors are equipped to disseminate best practices of bullying prevention to parents and increase school and home communication on effective bystander responses, but how much this influences what parents teach their children as bystanders is not clear. The current study examined whether parental perceptions of school climate and awareness of antibullying interventions affected what parents teach their children to do as bystanders to school bullying. Results indicated a significant and positive relationship between parent and school counselor agreement on the presence of antibullying interventions and parents teaching their children to stand up for the victim if they witness bullying at school. We discuss strategies to promote home and school collaboration on antibullying initiatives, extending the role of school counselors in antibullying efforts, and future directions.